Ensino dialógico e cultura científica na educação infantil: inter-relações mediadas pela linguagem - Arraes, Jéssica Palácio (2021)
Starting from the premise of a necessary and urgent change of educational paradigm in the information society, this research seek to demonstrate another possibility of pedagogical practice and its approach with the scientific knowledge, trying to identify the relations between childhood culture and scientific culture, besides the mediation of this possible interpenetration through the language and the horizontality of the relations between the subjects of the educational act - particularly students, teachers, family and community in general. For this from the perspective of narrative research we seek to analyze the dialogic interactions present in a teaching context in early childhood education at the Child Care Unit of the Federal University of São Carlos with children aged three to five years old and the practice based on the dialogic approach to teaching performed in this environment, at first, a face-to-face context and then with all the implications that the Covid-19 pandemic brought to the scenario of early childhood education amid a serious health, humanitarian and educational crisis.